An example of a stochastic differential equation with the property of weak non-uniqueness of a solution - Kopytko, B.I.; Portenko, M.I. (Інститут математики НАН України, 2006)
A family of one-dimensional diﬀusion processes is constructed such that each one of this family is a weak solution to some stochastic diﬀerential equation. It turns out that the property of weak uniqueness of a solution to this equation is failed.